2022
DOI: 10.26434/chemrxiv-2022-jntqv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Modeling of Conformer Stability in Benenodin-1, A Thermally-Actuated Lasso Peptide Switch

Abstract: Benenodin-1 is a thermally-actuated lasso peptide rotaxane switch with two primary translational isomers that differ in the relative position of residue Gln15. The conversion from one conformer to the other involves substantial enthalpy-entropy compensation: one conformer is energetically-favored and the other is entropically-favored. Here, we take a multi-scale quantum mechanical (QM) and classical molecular dynamics (MD) approach to reveal residue-specific sources of these differences in stability. QM reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Benenodin-1 conformer 2 involves a cis-isopeptide bond, 15 which was not considered in the current version of LassoHTP. For streptomonomicin, the NMR structure was determined in methanol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Benenodin-1 conformer 2 involves a cis-isopeptide bond, 15 which was not considered in the current version of LassoHTP. For streptomonomicin, the NMR structure was determined in methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies have elucidated the physical basis of folding, threading, and thermally-actuated switching for specific lasso peptides. 6,11,15,16 Ferguson et al showed that uncyclized microcin J25 can spontaneously adopt a left-handed coil configuration using replicaexchange molecular dynamics (MD). 6 Allen et al applied classical classical MD simulations with umbrella sampling to study the energetic preference of different pulling mechanisms for astexin-3 unthreading.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational studies have elucidated the physical basis of folding, threading, and thermally actuated switching for specific lasso peptides. 6,11,15,16 Ferguson et al showed that uncyclized microcin J25 can spontaneously adopt a left-handed coil configuration using replica-exchange molecular dynamics (MD). 6 Allen et al applied classical MD simulations with umbrella sampling to study the energetic preference of different pulling mechanisms for astexin-3 unthreading.…”
Section: Introductionmentioning
confidence: 99%